Selectivity Bias in Male Wage Equations: Black-White Comparisons - Hoffman, Saul D.; Link, Charles R. (The Review of Economics and Statistics, 1984)
Recent studies have documented a significant rise in the male black-white earnings ratio since the mid-1960s. The growing difference in nonemployment rates of blacks and whites clouds these optimistic findings. The basic question addressed in this paper is whether selectivity bias, caused by racial differences in employment rates, is a serious problem in the estimation of wage functions for adult males. For males age 21-34 we found no evidence of selectivity bias, but for the older cohort of males age 35-54, the results are quite different. For both whites and blacks, there is strong positive selection bias. It appears that biased estimates of several important coefficients are obtained using simple ordinary least squares procedures. The most interesting of these are the effect of low education for blacks.